A new algorithm of critical control rod position search in MC code - Li, Rui; Fu, Yuanguang; Liu, Peng; Shi, Dunfu; Deng, Li; Xu, Haibo (Annals of nuclear energy, 2024)
•Delayed material replacement is proposed to simulate control rod movement.•Combined with neutron balance, a new method is developed for criticality search.•Support Vector Regression is used in critical rod position calculation. Delayed Material Replacement algorithm is used in control rod movement simulation. Then, critical control rod position search is studied in Monte Carlo criticality calculation. Support Vector Regression algorithm is used in fitting neutron absorption as a function of rod positions. Fission iteration batches are reorganized as blocks in order to avoid fission source perturbation caused by control rod movement. The keff result in AP1000 reactor calculation shows discrepancy less than 20 pcm, though stable fluctuations are found in rod position values during fission iteration.